Exploring Islamic human values on self-regulation for career adaptability among Muslim millennials / Meita Triantiani, Olivia Fachrunnisa and Ardian Adhiatma - Triantiani, Meita; Fachrunnisa, Olivia; Adhiatma, Ardian (2022)
The Muslim millennials which refers to those who are Muslim with an age range of birth from 1982-2004, find it easy to change jobs when they feel that their jobs are not suitable for their abilities and interest. Therefore, to be able to face a dynamic and heterogeneous world of work, the application of Islamic human values in resilience and hardiness is important to help them adapt to their future career. Career adaptability is one of the abilities that can help Muslim millennials deal with the transition of environment from college to the work place, as even for a professional employee, being adaptive is still a challenge. Therefore, to be able to face a heterogeneous work environment in the future, the application of Islamic human values in their resilience and hardiness is important. The purpose of this study is to develop a model to improve the career adaptability of the Muslim millennial generation with the lens of Islamic Human Values in resilience and hardiness abilities. Data were collected from 150 of the Muslim millennial generation in one of the Islamic private universities at Semarang and there were two phases, the first phase was qualitative which was conducted by interview and observation and the second phase was quantitative by using a questionnaire. Data analysis tool used was Smart Partial Least Square (PLS) and the amount of data that can be used was 141. The study concludes that Islamic human values have positive significant influence on an individual’s resilience and hardiness. Furthermore, the resilience and hardiness influenced by Islamic human values have a positive significant effect on career adaptability.